Thermal oxidation of medical Ti6Al4V blasted with ceramic particles: Effects on the microstructure, residual stresses and mechanical properties. (February 2016) - Lieblich, M.; Barriuso, S.; Multigner, M.; González-Doncel, G.; González-Carrasco, J.L.
Abstract: Roughening of Ti6Al4V by blasting with alumina or zirconia particles improves the mechanical fixation of implants by increasing the surface area available for bone/implant apposition. Additional thermal oxidation treatments of the blasted alloy have already shown to be a complementary low-cost solution to enhancing the in vitro biocompatibility and corrosion resistance of the alloy. In this work, the effects of oxidation treatment on a grit blasted Ti6Al4V biomedical alloy have been analysed in order to understand the net effect of the combined treatments on the alloy fatigue properties. Synchrotron radiation diffraction experiments have been performed to measure residual stresses before and after the treatments and microstructural and hardness changes have been determined. Although blasting of Ti6Al4V with small spherical zirconia particles increases the alloy fatigue resistance with respect to unblasted specimens, fatigue strength after oxidation decreases below the unblasted value, irrespective of the type of particle used for blasting. Moreover, at 700 °C the as-blasted compressive residual stresses (700 MPa) are not only fully relaxed but even moderate tensile residual stresses, of about 120 MPa, are found beneath the blasted surfaces. Contrary to expectations, a moderate increase in hardness occurs towards the blasted surface after oxidation treatments. This can be attributed to the fact that grit blasting modifies the crystallographic texture of the Ti6Al4V shifting it to a random texture, which affects the hardness values as shown by additional experiments on cold rolled samples. The results indicate that the oxidation treatment performed to improve biocompatibility and corrosion resistance of grit blasted Ti6Al4V should be carried out with caution since the alloy fatigue strength can be critically diminished below the value required for high load-bearing components. Highlights: Thermal oxidation of blasted Ti6Al4V induces critical microstructural changes. Residual stress state changes from compressive to tensile at the subsurface. Fatigue strength of blasted alloy decreases sharply after thermal oxidation. Grit blasting modifies the crystallographic texture of the blasting affected zone.